Complete chloroplast genome of the plant Stahlianthus Involucratus (Zingiberaceae) - Li, Dong-Mei (Mitochondrial DNA B Resour, 2019)
The first complete chloroplast genome of Stahlianthus involucratus (Zingiberaceae) was reported in this study. The S. involucratus chloroplast genome was 163,300 bp in length and consisted of one large single copy (LSC) region of 87,498 bp, one small single copy (SSC) region of 15,568 bp, and a pair of inverted repeat (IR) regions 30,117 bp. It encoded 141 genes, including 87 protein-coding genes (79 PCG species), 46 tRNA genes (28 tRNA species) and 8 rRNA genes (4 rRNA species). The phylogenetic analysis based on single nucleotide polymorphisms strongly supported that S. involucratus, Curcuma roscoeana and Curcuma longa formed a cluster in group CurcumaII within family Zingiberaceae.